Petronio, Virgilio y el carácter de lo monstruoso en Adán Buenosayres (Argos, 2025)
ln several opportunities Leopoldo Marechal admitted his adhesion to the classification of genres according to Aristotelian criteria and, in particular, he pointed out that they belong to a poeticus labor. From this perspective, the novel is a legitimate substitute for the epic poem, whose canonical principles he followed to write Adán Buenosayres. Marechal does not confine intertextual relations to the recourse to The Stagirian's poetics, but by combining different procedures of hypertextual transformation, he devotes himself to a real generic contamination, enriching and proteic, which can be observed in the analysis of the diverse greco-latin hypotexts contained in chapter 7 of Book VII "Viaje a la oscura ciudad de Cacodelphia". Through the journey, Marechal will attempt to find the answers on the singular identity of the Argentines, transforming his novel into a true classical and medieval palimpsest, parodically grotesque and satiric.
Keywords: hypertextuality; generic contamination; parody; allusion; poetics